Exportin XPO6 upregulation activates the TLR2/MyD88/NF-κB signaling by facilitating TLR2 mRNA nuclear export in COPD pulmonary monocytes - Wu, Yuting; Gou, Yanni; Wang, Tao; Li, Ping; Li, Yongqiang; Lu, Xing; Li, Weifeng; Liu, Zhifeng (International immunopharmacology, 2024)
•Exportin XPO6 was upregulated in COPD pulmonary monocytes.•XPO6 promoted TLR2 expression in monocytes.•XPO6 enhanced MyD88/NF-κB inflammatory signaling via TLR2.•XPO6 facilitated TLR2 mRNA nuclear export in monocytes. Chronic obstructive pulmonary disease (COPD) poses a significant health threat characterized by lung inflammation primarily triggered by pulmonary monocytes. Despite the centrality of inflammation in COPD, the regulatory mechanisms governing this response remain elusive, presenting a challenge for anti-inflammatory interventions. In this study, we assessed the expression of exportins in COPD mouse models, revealing a notable upregulation of XPO6 in the mouse lung (P = 0.0011). Intriguingly, we observed a consistent upregulation of XPO6 in pulmonary monocytes from both human and mouse COPD subjects (P < 0.0001). Furthermore, in human lung tissue, XPO6 expression exhibited a positive correlation with TLR2 expression (P = 0). In vitro investigations demonstrated that XPO6 enhances TLR2 expression, activating the MyD88/NF-κB inflammatory signaling pathway. This activation, in turn, promotes the secretion of pro-inflammatory cytokines such as TNFα, IL-6, and IL-1β in monocytes. Mechanistically, XPO6 facilitates the nuclear export of TLR2 mRNA, ensuring its stability and subsequent protein expression in monocytes. In conclusion, our findings unveil that the upregulation of XPO6 in COPD pulmonary monocytes activates the MyD88/NF-κB inflammatory signaling pathway by facilitating the nuclear export of TLR2 mRNA, thereby identifying XPO6 as a promising therapeutic target for anti-inflammatory interventions in COPD.